LIMFOMA TESTIS NON HODGKIN METASTASIS KE LEPTOMENINGEAL OTAK DAN SPINAL - Serly, Reggy Panggabean, Tan Siaw Kwan, Els Anggraeni (NEURONA, 2012)
INTRODUCTION TESTICULAR LYMPHOMA IS A RARE NEOPLASM WHICH COMMONLY PRESENT IN ELDERLY PATIENTS AGE MORE THAN 60 YEARS THIS TYPE OF LYMPHOMA CAN METASTASIZE TO EXTRANODAL REGION INCLUDING THE CENTRAL NERVOUS SYSTEM IN THIS PAPER A YOUNG ADULT MALE PATIENT AGE 40 YEARS WITH TESTICULAR LYMPHOMA IS PRESENTED THE MALIGNANT CELLS SPREAD THORUGH CEREBROSPINAL FLUID AND CAUSED SUBDURAL AND CALVARIA METASTASIS THUS CAUSING THE PATIENT TO EXPERIENCE LEPTOMENINGIEAL SIGNS SUCH AS NUCHAL RIGIDITY AND HEADACHE THE MALIGNANCY ALSO SPREAD HEEMATOGENOUSLY TO THE VERTEBRA AND LYPHOGENOUSLY TO THE LEFT HEMIPELVIC LYMPH NODES AND RETROPERITONEUM